Public accounting firm recruiter attitudes toward the desirability of graduate characteristics - Ahmad, Saudah; Abdul Wahab, Nor Shaipah; Ahmad, Junaidah Hanim (Universiti Utara Malaysia, 2002)
The purpose of conducting this study is to determine the public accounting recruiters attitudes toward various graduate characteristics and to investigate whether there is a difference in relative importance attached to the characteristics among recruiters with different professional staff sizes. This study uses a questionnaire adopted from Schmutte (1998) with several modifications to better suit the Malaysian context. A total of 128 public accounting firms, which employed Universiti Utara Malaysia’s (UUM) students for the practicum programme were chosen as respondents. The findings reveal that there is no significant difference in recruiters’ attitude towards the desired characteristics. Secondly, written and verbal communication skills in English are the two most important characteristics demanded by recruiters. Attitude and personality traits are also ranked as highly important. Finally, it is found that firms with larger size of professional staff put more emphasis on outside interests and hobbies, accounting grade point average and the first five minutes of the interview. The findings help to conclude that all of the listed characteristics are important for entering the job market, regardless of the firms’ professional staff size. It can be said that accounting firms seek these characteristics while recruiting. Excellent English communication skills, personality and balance in both academic and co-curriculum activities are vital in ensuring that the graduates’ ability to enter the job market. Accounting educators and practitioners must collaborate to ensure that the students know and understand the profession’s demand. Accounting educators should also put more effort in preparing graduates with all the needed characteristics.